MUSLIM YOUTH ORGANIZATIONS IN BRITAIN - Sophie Gilliat (International Institute of Islamic Thought, 1997)
Muslim youth organizations reflect some of the most dynamic and important issues currently facing the British Muslim community. The question of young Muslims and the organizations in which they are involved must be a matter high on the agenda of all with an interest in the future of Islam in Britain. In talking about Muslim youth movements in the past and present, one is at the same time looking ahead into the next millennium: the picture is one of exciting new directions, uncertainty, threat, and promise. In the first part of this paper, I will examine the emergence and development of Muslim youth organizations in Britain, paying attention to questions such as their goals, membership, leadership, ethos, and activities. In the second section, I will assess what needs the different organizations appear to be fulfilling and, in this part of the paper, I will focus on issues relating to ideology, identity, belonging, the future of Islam, and the resolution of generational conflicts. As the discussion progresses, some assessment will be made of the significance of the different Muslim youth groups as elements of the wider Islamic community in this country and a consideration as to where they fit into the over-all structure of Muslim activity. It is not my intention to survey every youth movement that has ever existed and what their activities and ideologies have been. Instead, the focus will be on three major youth organizations, all of which contrast with each other in quite significant ways, and yet which share some common aspirations. In a sense, they will provide the context for the more theoretical second section of the discussion. By concentrating on three particular groups, a whole variety of other youth groups have ...